2017
DOI: 10.1002/adhm.201601022
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization of Nerve Interface via Biocompatible Polymer‐Roughened Pt Black on Cuff Electrode for Chronic Recording

Abstract: Peripheral nerve cuff electrodes with roughened Pt black (BPt) are coated with polyethylene glycol (PEG) and Nafion (NF). Although the influence of coated PEG and Nafion on roughened BPt on the electrical properties is weak, the cuff electrode with BPt/PEG and BPt/Nafion exhibits some very important properties. For example, it markedly decreases interfacial impedance, increases charge storage capacity (CSC) due to retaining the BPt surface structure, good stability without exfoliation in repetitive cyclic volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…To improve the long‐term functional outcome of implanted electrodes, different strategies have been developed. From the biomaterials field, different polymers (Sommakia et al, ; Skousen et al, ; Lee et al, ) and surface coatings (Cui et al, ; Balaji et al, ; Noorisafa et al, ) have been investigated to reduce the FBR. In fact, these coatings have been used as local delivery systems of active molecules or drugs to modulate the inflammatory reaction in subcutaneous (Norton et al, ; Hetrick et al, ) and brain (Mercanzini et al, ; Zhong et al, ) implants.…”
mentioning
confidence: 99%
“…To improve the long‐term functional outcome of implanted electrodes, different strategies have been developed. From the biomaterials field, different polymers (Sommakia et al, ; Skousen et al, ; Lee et al, ) and surface coatings (Cui et al, ; Balaji et al, ; Noorisafa et al, ) have been investigated to reduce the FBR. In fact, these coatings have been used as local delivery systems of active molecules or drugs to modulate the inflammatory reaction in subcutaneous (Norton et al, ; Hetrick et al, ) and brain (Mercanzini et al, ; Zhong et al, ) implants.…”
mentioning
confidence: 99%
“…The failure origin will be investigated, since the short lifetime of our sensor remains a limitation that will need to be improved for clinical applications. The sensor was designed from the start for implantation, and so all the outward facing materials were selected for their established biocompatibility, including silicon dioxide [52][53][54], Nafion [55][56][57], and Epotek OG116-31 epoxy resin. We have recently demonstrated that implantation of these sensor materials does not cause changes in tumour pathology [58], which will be essential for clinical deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Such metal coatings can increase the effective surface area while maintaining the geometric size of the electrodes, thereby reducing the impedance and increasing the charge storage capacity. Metals demonstrate good stability and benefit from a well-established preparation process, and they have been widely used for interfacial modification 19 21 , 23 . Titanium nitride has good conductivity, mechanical properties and stability.…”
Section: Basic Requirement: High-quality Recording Capabilitymentioning
confidence: 99%
“… Modified materials Examples Impedance at 1 kHz before modification (kΩ) Impedance at 1 kHz after modification (kΩ) Characteristics Refs. Metals Au nanoparticles 220.80 44.25 Larger surface area 19 Pt black 3.97 0.46 21 Metal nitrides TiN N/A 149 Larger surface area Excellent conductivity and stability 26 Carbon materials CNT-PEDOT 124.1 2.6 Larger surface area Superb adhesion 29 CNF-PEDOT 600 4.1 30 Graphene 0.00066 0.00036 32 Metal oxides IrOx 54.1 3.7 Good electrochemical activity Larger surface area 33 Conductive polymers PEDOT 700 10 Good electrochemical activity Larger surface area 35 PPy 800 80 41 …”
Section: Basic Requirement: High-quality Recording Capabilitymentioning
confidence: 99%